2007
DOI: 10.1159/000106576
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Thalidomide Therapy in Non-HIV-Related Kaposi’s Sarcoma

Abstract: Background: Thalidomide has antiangiogenic and immunomodulatory properties and has recently been used in the management of human malignancies. Several studies have suggested its interest for treating AIDS-related Kaposi’s sarcoma. Objectives: This study aimed to assess the efficacy and toxicity of thalidomide, an antiangiogenic agent, for the treatment of non-HIV-related Kaposi’s sarcoma. Methods: Eleven patients were included in this retrospective study conducted in the Department of Dermatology of Saint Loui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Out of these 14 patients, 4 (28%) discontinued thalidomide for side-effects. The overall response rate appears thus to be quite similar in KS, whether HIV associated or not, and lower than the response rates obtained with other systemic therapies such as interferon, pegylated liposomal doxorubicin [10] or even radiotherapy in localized cases [11] .…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Out of these 14 patients, 4 (28%) discontinued thalidomide for side-effects. The overall response rate appears thus to be quite similar in KS, whether HIV associated or not, and lower than the response rates obtained with other systemic therapies such as interferon, pegylated liposomal doxorubicin [10] or even radiotherapy in localized cases [11] .…”
mentioning
confidence: 73%
“…retrospective studies [9,10] . In the first study, Rubegni et al [9] treated 3 patients with 100 mg/day of thalidomide for 1 year and observed a complete response in 2 patients (including an immunosuppressed patient with systemic KS) and a partial response in the third.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Three patients achieved a PR and 4 had SD. Three of 11 patients (27%) prematurely discontinued thalidomide because of grade 1 sensory neuropathy and vertigo [28].…”
Section: Thalidomidementioning
confidence: 99%